Possession “Entangled” with Obligation - Nedev, Delyan (Research Papers, 2020)
The article examines the relation between possession and obligations and especially the possession acquired under preliminary contract (art. 70, para 3 of the Law of Property Act). The distinction is made between possession which can lead to acquisitive prescription and possession, incapable of causing that.
Keywords: Possession; Obligation; Preliminary contract; Acquisitive prescription